2017
DOI: 10.1088/1361-6668/aa9e17
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Josephson vortex two-state system based on a confocal annular Josephson junction

Abstract: We report theoretical and experimental work on the development of a Josephson vortex qubit based on a confocal annular Josephson tunnel junction (CAJTJ). The key ingredient of this geometrical configuration is a periodically variable width that generates a spatial vortex potential with bistable states. This intrinsic vortex potential can be tuned by an externally applied magnetic field and tilted by a bias current. The two-state system is accurately modeled by a one-dimensional sine-Gordon like equation by mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…4 . The experimental findings of this Section with no trapped field ratify once again that the effects of a transverse magnetic field applied to a Lyngby-type confocal AJTJ are in all respect comparable to those of an in-plane magnetic field applied in the direction of the bias current 16,17 . In other words, the radial distribution of the magnetic field induced by the shielding currents circulating on the outer borders of the top and bottom junction's electrodes is qualitatively similar to that created by an uniform in-plane magnetic field in the Y -direction.…”
Section: B Zero-field Coolingsupporting
confidence: 68%
See 2 more Smart Citations
“…4 . The experimental findings of this Section with no trapped field ratify once again that the effects of a transverse magnetic field applied to a Lyngby-type confocal AJTJ are in all respect comparable to those of an in-plane magnetic field applied in the direction of the bias current 16,17 . In other words, the radial distribution of the magnetic field induced by the shielding currents circulating on the outer borders of the top and bottom junction's electrodes is qualitatively similar to that created by an uniform in-plane magnetic field in the Y -direction.…”
Section: B Zero-field Coolingsupporting
confidence: 68%
“…These effects have been investigated both theoretically and experimentally for rectangular as well as for annular junctions [13][14][15] ; furthermore, it has been demonstrated that for AJTJs made by specularly symmetric electrodes a transverse magnetic field is equivalent to an in-plane field applied in the direction of the current flow. The transverse critical field is much smaller than its in-plane analog 16,17 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…More details on the samples description end their fabrication were reported, respectively, in Ref. 28 and Ref. 43 .…”
Section: The Measurementsmentioning
confidence: 99%
“…It is this smooth periodic change of the width of the planar tunnel barrier that makes the physics of CAJTJs very rich and interesting especially since the modeling is very accurate 20,27 . Recently 28 , experiments have shown that a fluxon trapped in a long and narrow CAJTJ experiences a finely tunable DWP and both the preparation and readout of the vortex states in either the left or right state, that are important with respect to the possible realization of a vortex qubit, can be achieved by simple and robust procedures. The previously presented findings concerned CAJTJs with the moderate aspect ratio of 2 : 1 in which, as in Fig.…”
Section: Introductionmentioning
confidence: 99%